Direct and long-term detection of gene doping in conventional blood samples - Beiter, T.; Zimmermann, M.; Fragasso, A.; Hudemann, J.; Niess, A. M.; Bitzer, M.; Lauer, U. M.; Simon, P. (Gene Therapy, 2010)
The misuse of somatic gene therapy for the purpose of enhancing athletic performance is perceived as a coming threat to the world of sports and categorized as `gene doping`. This article describes a direct detection approach for gene doping that gives a clear yes-or-no answer based on the presence or absence of transgenic DNA in peripheral blood samples. By exploiting a priming strategy to specifically amplify intronless DNA sequences, we developed PCR protocols allowing the detection of very small amounts of transgenic DNA in genomic DNA samples to screen for six prime candidate genes. Our detection strategy was verified in a mouse model, giving positive signals from minute amounts (20 microliter) of blood samples for up to 56 days following intramuscular adeno-associated virus-mediated gene transfer, one of the most likely candidate vector systems to be misused for gene doping. To make our detection strategy amenable for routine testing, we implemented a robust sample preparation and processing protocol that allows cost-efficient analysis of small human blood volumes (200 microliter) with high specificity and reproducibility. The practicability and reliability of our detection strategy was validated by a screening approach including 327 blood samples taken from professional and recreational athletes under field conditions.